Larval dynamics suggest phenological strategies and positive effect of marine protected areas controlling indigenous and non-indigenous crab populations - Landeira, José M.; Fatira, Effrosyni; Cuesta, Jose A.; Schubart, Christoph D.; Moreno-Borges, Sergio; Rodríguez, Adriana (Frontiers in Marine Science, 2024)
The early life of most decapod crustaceans takes place in the water column as larvae before they settle in benthic habitats. The spatial and temporal variability in the settling of larval stages offers valuable insights into the potential recruitment of natural populations. To explore this, we studied megalopa assemblages at various segments of coastline on El Hierro and Lanzarote islands, both within and outside the Marine Protected Areas (MPAs) of each island. The study spanned four consecutive oceanographic periods in the Canary Islands (NW Africa), employing light traps for sample collection. The low number of recorded species suggested that light traps exhibit selectivity, particularly for megalopae belonging to Portunidae and Grapsidae. El Hierro, which experienced warmer sea surface temperatures, displayed higher megalopa abundance values than Lanzarote and distinct larval assemblages was observed between these two islands. Similarly, we identified significant variations in abundance and species composition between stratified and mixing seasons. These seasonal differences were influenced by the dominance of Achelous hastatus, Percnon gibessi, and Cronius ruber during the stratified season. In Lanzarote, C. ruber was not recorded during the mixing season, suggesting that the colder conditions there may constrain its reproduction. Interestingly, we observed that species traditionally harvested from the intertidal zone for human consumption (Plagusia depressa) or used as bait for recreational fishing (Pachygrapsus spp. and P. gibessi) exhibited higher megalopa abundances within the MPAs. In contrast, we noted lower megalopa densities of the non-indigenous species C. ruber within the protected areas. These results indicate a positive effect of MPAs controlling indigenous and non-indigenous crab populations. Moreover, the study provides novel data, showing that light traps are suitable for monitoring the temporal occurrence, abundance, and spatial distribution of non-indigenous and commercially exploited species. This is key for adopting an ecosystem-based approach to manage marine resources.